2019
DOI: 10.1088/1475-7516/2019/06/042
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on axion-like particle properties with TeV gamma-ray observations of Galactic sources

Abstract: Axion-like particles (ALPs) can oscillate to photons and vice versa in electromagnetic fields. The photon-ALP oscillation provides an attractive solution to the apparent transparency of the Universe to TeV photons. The allowed parameter regions for the ALP mass m a ≤ 10 −7 eV have been tightly constrained by the Fermi-LAT and H.E.S.S observations of some extragalactic sources. In this work we show for the first time that the H.E.S.S observations of some TeV sources in the Galactic plane exclude the highest ALP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 84 publications
(201 reference statements)
2
31
0
Order By: Relevance
“…[52], Faraday rotation mapping of the Perseus cluster looks a promising way to obtain better constraints on the magnetic field in the region where the lobes of NGC 1275 interact with the intracluster matter. In addition, sources embedded in magnetic fields better studied observationally may be invoked for the search of irregularities, for instance M 87 [39] and Galactic sources [32,33,34]. For certain values of ALP parameters, the transition to the regime of strong mixing in the Galactic magnetic field may be observed or constrained also for extragalactic sources, cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52], Faraday rotation mapping of the Perseus cluster looks a promising way to obtain better constraints on the magnetic field in the region where the lobes of NGC 1275 interact with the intracluster matter. In addition, sources embedded in magnetic fields better studied observationally may be invoked for the search of irregularities, for instance M 87 [39] and Galactic sources [32,33,34]. For certain values of ALP parameters, the transition to the regime of strong mixing in the Galactic magnetic field may be observed or constrained also for extragalactic sources, cf.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to follow this way have been made in recent years, exploiting the observed smoothness of X-and gammaray spectra of strong emitters presumably embedded in astrophysical magnetic fields. In particular, these included analyses of gamma-ray observations of PKS 2155−304 [27,28,29], NGC 1275 [30,31] and several Galactic sources [32,33,34] relevant for ALP masses ∼ 10 −9 − 10 −7 eV (overlapping with the range invoked for explanations of the "anomalous transparency" effects). For lower ALP masses, X-ray observations of 3C 218 [35], the same NGC 1275 [36,37,38], M 87 [39] and some other extragalactic sources [40] were used.…”
Section: Introductionmentioning
confidence: 99%
“…By summing the ∆χ 2 value of all the three SNRs, we derive combined constraints on ALP parameters. Some studies [26,33] have shown that, due to the complexity between ALP parameters and spectral irregularities, the ∆χ 2 distribution in the null hypothesis is not as expected by Wilks theorem [65] to be a χ 2 distribution with 2 degree of freedom. We thus perform Monte Carlo (MC) simulation to derive the null distribution and the threshold value of ∆χ 2 .…”
Section: Combined Limits Of All the Three Snrsmentioning
confidence: 95%
“…The large-scale Galactic magnetic field model developed by Jansson & Farrar [51] (Bfield1) is adopted in our work, which has been wildly used in the relevant investigations [29][30][31][32][33]. This model composes of a disk field, an extended halo field and out of plane component and provides a best fit to WMAP7 Galactic synchrotron emission map and more than 40,000 extragalactic rotation measures (RM) data.…”
Section: Photon-alp Oscillation In the Milky Way Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation